"The future of media studies is game studies". Issue 3 (27th May 2022) - Chess, Shira; Consalvo, Mia
ABSTRACT: Game studies, as a subfield of media and/or communication studies, has occupied an odd place within critical media studies. Those who are invested in critical theory of video game studies understand the importance of the subfield, those who do not study or play video games tend to think of the topic as "other"—as distinct from other theoretical compartments of media studies work. Yet, as the games scholars in this invited issue explain, games are now a central component in the convergence of media content, media platforms and technologies, and media audiences. Theories and methods that help us understand games and their culture are therefore increasingly relevant to understanding wider media production and use. The goal with this special issue, therefore, was to offer a variety of approaches and specifics that would be helpful to scholars both within and beyond game studies.